Mewujudkan Sistem Peradilan Pidana Terpadu Melalui Case Management System (Studi di Kejaksaan Negeri Kota Bogor) - E. Agus Suryadi; H. Supardi (Universitas Negeri Surabaya, 2021)
This legal writing motivated by the efforts made by the Bogor City State Prosecutors Office in order to make changes by implementing information technology innovations in handling general criminal cases, especially the handling of narcotics and psychotropic cases in order to realize good and professional governance. System, reduce abuse of power, and curb case administration from the SPDP stage to the implementation stage. The outline of this paper is to discuss the issue of implementing the Case Management System (CMS) in the data input process for handling narcotics and psychotropic crime cases at the Bogor City District Attorneys Office in realizing an integrated criminal justice system. This research uses statutory, case, comparative, and conceptual approaches. The results showed that the data input process for handling cases of narcotics and psychotropic crimes was in accordance with the SOP, the application of an integrated case handling system in the Information Technology Integrated Case Management System (SPPT-TI) so that it could increase efficiency and effectiveness in case handling. However, there are still obstacles that were face, namely the lack of operator personnel and a lack of understanding of the application of the use of the Case Management System (CMS), but with these obstacles, training on CMS data entry conducted.